SENTRA GALERI KERAJINAN TENUN KALIMANTAN BARAT DI KOTA PONTIANAK - Eriyanty, Elen; Affrilyno, Affrilyno; Caesariadi, Tri Wibowo (JMARS: Jurnal Mosaik Arsitektur, 2020)
Local residents of West Borneo have expertise in producing variety of traditional crafts, one of which is woven fabrics, which is no less competitive with other regions. But there are several problems regarding the lack of facilities and infrastructure, such as less productive weaving processes, exhibitions that are held irregularly, difficulty of marketing products and no place for discussion. Therefore, the need of a place to product, exhibit, and market the products of West Borneo woven fabrics called "Center of West Borneo Weaving Craft Gallery in Pontianak" is essential. The design process starts from the analysis of functions which are divided into 3 groups, such as the main function group is commercial function, the extension function group is to produce recreation, education and performance function, while the other support function group is to produce management and service functions. The design applies theme of contemporary architecture as an approach that will support the creation of spaces that have harmonization, interactive, innovative and iconic concepts. The appeal of the idea design building shape is the philosophy of the analogy from winding’s tool which is divided into three parts and produces the main building, workshop building and multipurpose building. The number of floors for each building is almost the same which is two floors, except for the multipurpose building, which is one floor. The line movement from height of the building mass illustrates the existence of sustainability by creating an environment that represents aesthetic value and the harmonization of local culture to modernization.